QUALITY OF EDUCATION IN THE DEVELOPMENTAL ASPECT LEARNING FUNCTIONS (Pedagogy of Higher and Secondary Education, 2009)
he article deals with procedure of quality of education evaluation in the copect of developing function in learning.